A Meta‐Analysis on the Impact of Alcohol Dependence on Short‐Term Resting‐State Heart Rate Variability: Implications for Cardiovascular Risk. (26th July 2012) - Quintana, Daniel S.; McGregor, Iain S.; Guastella, Adam J.; Malhi, Gin S.; Kemp, Andrew H.
Abstract : Background: Alcohol dependence is associated with an increased likelihood of cardiac events. Reductions in heart rate variability (HRV) may be one mechanism linking dependence with these events. HRV may also be related to poor social functioning and the lack of impulse control commonly observed in alcohol‐dependent individuals. However, prior studies on the impact of alcohol dependence on HRV have reported contradictory findings highlighting the need for a meta‐analysis. Methods: Studies comparing short‐term HRV in alcohol‐dependent populations and healthy controls who were nondependent were considered for meta‐analysis. Only studies reporting findings from participants without cardiovascular disease were included in the analysis. Results: Meta‐analyses were based on 6 articles that fulfilled inclusion criteria, comprising a total of 177 alcohol‐dependent participants and 216 nondependent participants. Alcohol‐dependent participants displayed reduced HRV (Hedges' g = −0.6, p > 0.001) in comparison with nondependent participants. No differences were observed between the summary effect sizes obtained from different HRV domains ( Q = 1.19, p = 0.55). Conclusions: Alcohol dependence is associated with reduced HRV, an effect associated with a medium effect size. Findings highlight the importance of monitoring alcohol‐dependent patients for cardiac disease and emphasize the need for cardiovascular risk reduction strategies in these patients.